2008
DOI: 10.1161/circresaha.108.175307
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic and Endothelial Cell Adhesions via N-Cadherin Determine Polarity and Regulate Migration of Vascular Smooth Muscle Cells

Abstract: Abstract-Migration of smooth muscle cells from the arterial media to the intima is central to several vascular pathologies including restenosis. This study demonstrates that, like directional migration of other cells, smooth muscle migration is accompanied by a dramatic, polarized reorganization of the cell cytoskeleton that is accompanied by activation of the Rho GTPase Cdc42 and inactivation of glycogen synthase kinase-3␤. We also show, for the first time, that signals generated at the posterior-lateral aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 34 publications
6
42
0
Order By: Relevance
“…We have previously shown that, following wounding, Cdc42 is activated and recruited to the leading edge of migrating astrocytes in a wound-healing assay and that localized activity of Cdc42 plays a key role in astrocyte polarization and directed migration (Etienne-Manneville and Hall, 2001;Osmani et al, 2010;Osmani et al, 2006). In agreement with a recent study realized in smooth muscle cells, by using a blocking antibody against N-cadherin (Sabatini et al, 2008), we show here that intercellular contacts are required for the recruitment and activation of Cdc42 at the leading edge in response to the wound. Active Cdc42 induces the recruitment and activation of the Par6-PKCf polarity complex (EtienneManneville and Hall, 2001) and APC clustering at microtubule plus-ends (Etienne-Manneville and Hall, 2003).…”
Section: Cadherin-integrin Interplay In the Control Of Glial Cell Migsupporting
confidence: 88%
“…We have previously shown that, following wounding, Cdc42 is activated and recruited to the leading edge of migrating astrocytes in a wound-healing assay and that localized activity of Cdc42 plays a key role in astrocyte polarization and directed migration (Etienne-Manneville and Hall, 2001;Osmani et al, 2010;Osmani et al, 2006). In agreement with a recent study realized in smooth muscle cells, by using a blocking antibody against N-cadherin (Sabatini et al, 2008), we show here that intercellular contacts are required for the recruitment and activation of Cdc42 at the leading edge in response to the wound. Active Cdc42 induces the recruitment and activation of the Par6-PKCf polarity complex (EtienneManneville and Hall, 2001) and APC clustering at microtubule plus-ends (Etienne-Manneville and Hall, 2003).…”
Section: Cadherin-integrin Interplay In the Control Of Glial Cell Migsupporting
confidence: 88%
“…PKC isoforms regulating polarity include atypical aPKC, 2 PKC␤, 3-5 PKC, 6 and PKC␦. 5 We have recently shown that the MTOC is oriented anterior of the nucleus (ie, front polarized) in migrating medial SMCs in vitro, 7 which is in accord with other studies of cells migrating in two-dimensional culture. 8 -14 Little is known about polarization of the MTOC in vivo, where cells migrate in three dimensions.…”
supporting
confidence: 84%
“…Similarly, during neural crest cell migration, N-cadherin-mediated cell-cell adhesion has been shown to suppress membrane extensions by inhibiting Rac1 activity, so that the protrusions develop from the contact free edge (Theveneau et al, 2010). In addition, N-cadherin-mediated cell-cell adhesion is required for cell polarization and directional migration of vascular smooth muscle cells (Sabatini et al, 2008). Therefore, this N-cadherin-mediated contact inhibition may be what distinguishes the roles of leader vs. follower cells during collective migration of N-cadherin expressing cells.…”
Section: Discussionmentioning
confidence: 99%